GC-MS Profile of Hua-Feng-Dan and RNA-Seq Analysis of Induced Adaptive Responses in the Liver - Liu, Jia-Jia; Liang, Yan; Zhang, Ya; Wu, Rui-Xia; Song, Ying-Lian; Zhang, Feng; Shi, Jing-Shan; Liu, Jie; Xu, Shang-Fu; Wang, Zhang (Frontiers in Pharmacology, 2022)
Background: Hua-Feng-Dan is a patent Chinese medicine for stroke recovery and various diseases. This study used GC-MS to profile its ingredients and RNA-Seq to analyze the induced adaptive response in the liver. Methods: Hua-Feng-Dan was subjected to steam-distillation and solvent extraction, followed by GC-MS analysis. Mice were orally administered Hua-Feng-Dan and its “Guide drug” Yaomu for 7 days. Liver pathology was examined, and total RNA isolated for RNA-Seq, followed by bioinformatic analysis and quantitative real-time PCR (qPCR). Results: Forty-four volatile and fifty liposoluble components in Hua-Feng-Dan were profiled and analyzed by the NIST library and their concentrations quantified. The major components (> 1%) in volatile (5) and liposoluble (10) were highlighted. Hua-Feng-Dan and Yaomu at hepatoprotective doses did not produce liver toxicity as evidenced by histopathology and serum enzyme activities. GO Enrichment revealed Hua-Feng-Dan affected lipid homeostasis, protein folding and cell adhesion. KEGG showed activated cholesterol metabolism, bile secretion and PPAR signaling pathways. Differential expressed genes (DEGs) were identified by DESeq2 with p < 0.05 compared to controls. Hua-Feng-Dan produced more DEGs than Yaomu. qPCR on selected genes largely verified RNA-Seq results. Ingenuity Pathways Analysis of upstream regulator revealed activation of MAPK and adaptive responses by Hua-Feng-Dan, and Yaomu was less effective. Hua-Feng-Dan induced DEGs were highly correlated with the Gene Expression Omnibus database of chemical-induced adaptive transcriptome changes in the liver. Conclusions: GC-MS primarily profiled volatile and liposoluble components in Hua-Feng-Dan. Hua-Feng-Dan at hepatoprotective dose did not produce liver pathological changes but induced metabolic and signaling pathway activations. The effects of Hua-Feng-Dan on liver transcriptome changes point towards induced adaptive responses to program the liver to produce hepatoprotective effects.